THE REVIEW OF INTERNATIONAL LAW ON THE CAUSES OF THE RUSSIA-UKRAINE CONFLICT - Mdzinarshvili Mdzinarshvili; Siti Sa'atun (UNISSULA, 2022)
This research is to find out the cause of the war between Russia and Ukraine that just started on Thursday, February 24, 2022. This war took place after months of increasing tensions between the two countries. On Monday, February 21, Russian President Vladimir Putin acknowledged the creation of two states in the separatist region of eastern Ukraine. Then what is the background of the conflict in Ukraine which is now expanding into a West-Russian escalation. In February 2014, pro-Moscow Ukrainian President Viktor Janukovich was ousted from power by mass protests in the capital Kiev. Previously, Janukovich refused to sign an association agreement between Ukraine and the European Union under Russian pressure. The refusal has angered many citizens who are already excited about joining the European Union. Moreover, there were many accusations of corruption of government officials, including Viktor Janukovich, who eventually fled to Russia. Russia retaliated by sending troops to the Crimean Peninsula. After taking control of Crimea, Russia has fomented a separatist insurgency in the mostly Russian-speaking eastern Ukraine, known as the Donbas region, by sending weapons to the separatists. This study uses a Historical Normative approach by collecting various literatures as the main source. The results of the analysis show that in April 2014, Russian-backed rebels seized government buildings in the Donetsk and Luhansk regions, and proclaimed the creation of two new republics. The following month, the two separatist territories applied to become part of Russia. But Moscow has not officially responded to the request. Russia is known to want to prevent Ukraine from becoming a member of NATO, like other Eastern European countries. In conclusion Moscow also denies sending troops and weapons to eastern Ukraine, saying that Russian citizens fighting in eastern Ukraine are volunteers to prevent the genocide of the Ukrainian government.